The Washington Manual of Medical Therapeutics - Foster, Corey (Washington University School of Medicine, 2010)
The Washington Manual of Medical Therapeutics provides an easily accessible source of current information that covers a practical clinical approach to the diagnosis, investigation, and treatment of common medical conditions that internists encounter on a regular basis.